2019
DOI: 10.1111/1747-0080.12565
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of energy intake under‐reporting among Australian adults in 1995 and 2011 to 2012

Abstract: Aim Misreporting of energy intake is a common source of measurement error found in dietary surveys, resulting in biased estimates and a reduction in statistical power. The present study aims to refine the conventional cut‐off methods and to examine the extent to which Australian adults misreport their energy intake, and the characteristics of under‐reporters between two time points. Methods A revised Goldberg cut‐off approach was used to identify those who reported implausible intake amounts in a secondary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…The current analysis examined data was neither randomized nor blinded, and therefore the potential effects of conscious or unconscious bias cannot be discounted. Another limitation is the use of 24 h recall to assess adherence to the dietary plan, which is known to be biased by misreporting [31,32], specifically underreporting. Due to this limitation, which is difficult to overcome, it is not possible to properly assess the role that different energy intakes affected weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The current analysis examined data was neither randomized nor blinded, and therefore the potential effects of conscious or unconscious bias cannot be discounted. Another limitation is the use of 24 h recall to assess adherence to the dietary plan, which is known to be biased by misreporting [31,32], specifically underreporting. Due to this limitation, which is difficult to overcome, it is not possible to properly assess the role that different energy intakes affected weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Despite continued calls for research to better understand the psychosocial correlates of underreporting and differential reporting, there has been no substantial new work in this area over the past decade. Studies continue to focus on characterizing underreporters and describing associations, rather than delving into psychological processes and interaction of influencing factors [8,10,[12][13][14][36][37][38][39]. No studies were identified over the last 5 years that included interviews, focus groups, or other qualitative measures to better understand the psychosocial factors underlying underreporting of dietary intake among people with obesity.…”
Section: Why Do People Underreport Dietary Intake?mentioning
confidence: 99%
“…Of note was that the increase in under-reporting was largely in men, rising from 24% to 41%, in contrast to women where it remained constant at around 40%. 2 By comparison in a small sample of women with PCOS (n = 36) and control women (n = 37) energy under-reporting was identified for 47.2% of women with PCOS vs 2.7% among controls. 3 Women kept a 3-day food diary and individual level PAL factors were applied to identify mis-reporters using the Goldberg cut-off method.…”
Section: Introductionmentioning
confidence: 98%
“…Both surveys were administered face‐to‐face by interviewers and although 1995 was “pen and paper”, you would not expect this increase to be attributed to the interviewer's use of a computer to administer the recall in 2011‐12. Of note was that the increase in under‐reporting was largely in men, rising from 24% to 41%, in contrast to women where it remained constant at around 40% …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation